اسلام کا تصوّر انسان اور اس کی ذمّہ داریاں ایک تحقیقی جائزہ: Islamic Concept of Man and his Responsibilities - Kaukab, Tasmia (Al-Amīr Research Journal for Islamic Studies, 2020)
Allah Almighty has completed this world by the creation of human being. He Almighty has made the men superior than the other creation of all the world .By his creation Allah Almighty has designated some responsibilities to him as well. If He will fulfil these responsibilities and do right deed, Allah almighty will pleased by him and he will deserve the Heaven and if he will not fulfil his responsibilities which were designated by Allah almighty and will misconduct, then due to misconducting of his deeds he will go to Hell. By this article, I tried to describe the meaning of man and point out the process and stages of creation of human, his responsibilities and some hidden but bitter facts about human life. When a person accept and understand these facts, his life will be easy. In this research paper descriptive method of research has been adopted by researcher